Regulation of cellular cholesterol distribution via non-vesicular lipid transport at ER-Golgi contact sites - Naito, Tomoki (2023)
Abnormal distribution of cellular cholesterol is associated with numerous diseases, including cardiovascular and neurodegenerative diseases. Regulated transport of cholesterol is critical for maintaining its proper distribution in the cell, yet the underlying mechanisms remain unclear. Here, we show that lipid transfer proteins, namely ORP9, OSBP, and GRAMD1s/Asters (GRAMD1a/GRAMD1b/GRAMD1c), control non-vesicular cholesterol transport at points of contact between the ER and the trans-Golgi network (TGN), thereby maintaining cellular cholesterol distribution. ORP9 localizes to the TGN via interaction between its tandem α-helices and ORP10/ORP11. ORP9 extracts PI4P from the TGN to prevent its overaccumulation and suppresses OSBP-mediated PI4P-driven cholesterol transport to the Golgi. By contrast, GRAMD1s transport excess cholesterol from the Golgi to the ER, thereby preventing its build-up. Cells lacking ORP9 exhibit accumulation of cholesterol at the Golgi, which is further enhanced by additional depletion of GRAMD1s with major accumulation in the plasma membrane. This is accompanied by chronic activation of the SREBP-2 signalling pathway. Our findings reveal the importance of regulated lipid transport at ER-Golgi contacts for maintaining cellular cholesterol distribution and homeostasis.